Cyber-Proletariat : global labour in the digital vortex - Dyer-Witheford, Nick, 1951- (Digital Barricades: Interventions in Digital Culture and Politics, 2015)
"This book examines how technology facilitates growing polarisation between wealthy elites and precarious workers. Nick Dyer-Witheford reveals the class domination behind everything from expanding online surveillance to intensifying robotisation. At the same time, he explores the possibilities that information technology offers within radical movements, recasting contemporary struggles in the blue glow of the computer screen."